Discourse analysis a resource book for students - Jones, Rodney H. (Routledge English language introductions, 2019)
"Discourse Analysis, 2nd Edition: - provides a comprehensive overview of the major approaches to and methodological tools used in discourse analysis; - introduces both traditional perspectives on the analysis of texts and talk as well as more recent approaches that address technologically mediated and multimodal discourse; - incorporates practical examples using real data; - includes new articles from key authors in the field, including Jan Blommaert, William Labov, Paul Baker, Penelope Brown and Stephen Levinson; - is supported by a companion website featuring extra activities, additional guidance, useful links and multimedia examples including sound files and YouTube videos. Features of the new edition include: new readings featuring cutting-edge research; updated references; revised and refreshed examples; and a wider range of material from social media that includes Twitter, Instagram and Snapchat. Written by an experienced teacher and author, this accessible textbook is essential reading for all students of English language and linguistics"-- Provided by publisher.